Adaptation barriers and strategies towards climate change: Challenges in the agricultural sector. (10th July 2017) - Masud, Muhammad Mehedi; Azam, Mohammad Nurul; Mohiuddin, Muhammad; Banna, Hasanul; Akhtar, Rulia; Alam, A.S.A. Ferdous; Begum, Halima
Abstract: This paper explores farmers' perceptions of climate change vulnerability as well as the effects of socioeconomic factors and adaptation barriers on climate change adaptation practices in the Malaysian agricultural sector. To accomplish these aims, a multiple regression analysis was performed, and the severity index (SI) was estimated to measure perceived vulnerability context. The results revealed that age, education level, farm income, farm experience, limited access to agricultural extension, lack of credit facilities, limited access to agricultural markets, and farm size are factors which have significant impacts on adaptation practices. The value of the SI suggests that farmers have favourable attitudes towards climate change adaptation and they are agreeable to addressing climate change issues through appropriate adaptation strategies. However, the study found several adaptation barriers that hinder farmers from implementing climate change adaptation policies. It is realized that at present, no specific policy in Malaysia seeks to counter the impacts of climate change on individual sectors and their productivity. Therefore, the findings of this study will assist policymakers to make an appropriate policy framework considering most suitable adaptation strategies to overcome all the barriers associated with adaptation practices to tackle the adverse effects of climate change in Malaysian agriculture sector. Highlights: The study measures perceived vulnerability context based on the severity index (SI). The results show that socio-demographic factors have significant impacts on adaptation practices. The study highlights several adaptation barriers towards climate change which are faced by farmers. The findings help policymakers to plan a desirable climate change adaptation policy framework.